Isu Kontemporer dalam Linguistik Arab: Telaah Fenomena Diglosia, Bilingualisme, dan Perspektif Sosiolinguistik - Fajr, Rizka Al; Khairani, Putri Dian; Manalu, Samsia; Arifin, Jaenal; Susiawati, Iis (INCARE, International Journal of Educational Resources, 2025)
This study discusses the dynamics of language use in contemporary Arab society by examining the phenomenon of diglossia and bilingualism from a sociolinguistic perspective. Diglossia refers to the functional division between Modern Standard Arabic (fusha) used in formal domains and local dialects (‘ammiyah) utilized in daily communication. This linguistic situation not only reflects structural differences but also indicates social status, identity, and cultural values within society. Meanwhile, globalization, technological development, and cross-cultural interaction have contributed to the rise of bilingualism, particularly through the widespread use of English in education, media, and professional fields. These conditions further encourage linguistic behaviors such as code-switching and code-mixing in various communication contexts. Through library research, this study highlights how both phenomena shape the evolution of Arabic in the digital era. The findings reveal that Arabic continues to adapt to modern communication needs while maintaining its role as a language of knowledge and religious identity. Therefore, strengthening the use of fusha in education and formal communication is necessary, alongside recognizing the existence of dialects and foreign language influence as part of the living linguistic reality in Arab society today.